2001
DOI: 10.1590/s0006-87052001000300010
|View full text |Cite
|
Sign up to set email alerts
|

Índices De Eficiência De Variedades Locais E Melhoradas De Milho Ao Fósforo

Abstract: Avaliaram-se dez variedades locais e melhoradas de milho (Zea mays L.) a fim de verificar sua eficiência ao fósforo (P) em solução nutritiva e em campo. Em solução nutritiva, o experimento foi realizado no Instituto Agronômico, Campinas (SP), durante 1995-1996; o delineamento adotado foi o de em blocos ao acaso, com cinco repetições. Os tratamentos, dispostos em fatorial, constituíram-se de três concentrações de P (0,0645; 0,129 e 0,258 mmol.L-1) e dez variedades de milho. Em campo, o experimento foi instalado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0
14

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 24 publications
(40 reference statements)
6
27
0
14
Order By: Relevance
“…From around 8 mg L -1 , the root/shoot ratio was nearly stable up to the highest P level. The hagler root/shoot ratio observed at low than at higher P levels corroborated a number of studies (Balemi & Schenk, 2009;Machado et al, 2001;Hu et al 2010) and is related to a severe decrease in shoot DM compared to root DM ( Figure 1a,d). According to Cakmak et al (1994), the drastically reduced leaf development at low P levels results in a lower leaf demand for photoassimilates, leading to a higher translocation thereof to roots growth.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…From around 8 mg L -1 , the root/shoot ratio was nearly stable up to the highest P level. The hagler root/shoot ratio observed at low than at higher P levels corroborated a number of studies (Balemi & Schenk, 2009;Machado et al, 2001;Hu et al 2010) and is related to a severe decrease in shoot DM compared to root DM ( Figure 1a,d). According to Cakmak et al (1994), the drastically reduced leaf development at low P levels results in a lower leaf demand for photoassimilates, leading to a higher translocation thereof to roots growth.…”
Section: Resultssupporting
confidence: 88%
“…As lower levels drastically reduced shoot DM (Figure 1d), more P was allocated in roots to ensure growth (Figure 1a). Machado et al (2001) also found that maize plants proportionally allocated more P in roots, at the expense of shoots, at the lowest level in solution. According to Marschner (1995), P retention in roots is improved at insufficient levels, leading to redistribution via phloem and the supply of additional P.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Têm sido relatadas grandes diferenças entre as cultivares de milho, quanto à eficiência de utilização de P, o que resulta em variações de resposta à aplicação desse nutriente (Machado et al, 1999(Machado et al, , 2001.…”
Section: Introductionunclassified
“…Root morphological traits, such as total root length, total root surface, root diameter and root hair density are related to P uptake in maize and depend on the plant genotype (Machado et al, 2001). In turn, AMF and diazotrophic bacteria may affect root morphological traits.…”
Section: Introductionmentioning
confidence: 99%